Investigating the reassortment potential and pathogenicity of the S segment in Akabane virus using a reverse genetics system - Eun-Jee Na; Chang-Gi Jeong; Su-Beom Chae; Jae-Ku Oem (BMC Veterinary Research)
Abstract Background Akabane virus (AKAV) is an arthropod-borne virus that causes congenital malformations and neuropathology in cattle and sheep. In South Korea, AKAVs are classified into two main genogroups: K0505 and AKAV-7 strains. The K0505 strain infects pregnant cattle, leading to fetal abnormalities, while the AKAV-7 strain induces encephalomyelitis in post-natal cattle. The pathogenicities of K0505 and AKAV-7 strains differ significantly; however, the specific gene in the AKAV-7 strain that drives its pathogenicity remains unidentified. In this study, changes in viral replication and pathogenicity were investigated, particularly when the S segment of AKAV-7 was mutated using a T7 RNA polymerase-based reverse genetics (RG) system. Results The rAKAV-7ΔNSs virus, with a deletion in the NSs protein of the wild-type AKAV-7 virus (wtAKAV-7), and the rAKAV-7(S-K0505) virus, where the S segment of wtAKAV-7 was reassorted with that from the wild type K0505 strain (wtK0505), were successfully rescued. The rAKAV-7ΔNSs virus demonstrated impaired replication in Vero cells and exhibited reduced mortality and RNA viral load in the organs of suckling mice compared to the wtAKAV-7. The rAKAV-7(S-K0505) virus displayed similar growth kinetics in Vero cells and showed no significant reduction in mortality rate in suckling mice compared to wtAKAV-7. Conclusions These observations suggest that the S segment, especially the NS protein, is associated with the pathogenicity of AKAV-7. Also, the results imply that the L and M segments might explain the differences in pathogenicity between the AKAV-7 and K0505 strains. Moreover, our findings indicate the potential for reassortment between distinct genogroups of AKAVs.